Hurricane Katrina the storm that changed America - Marsalis, Wynton 1961- (Time Books, 2005)
On September 2, 2005, New Orleans Mayor Ray Nagin issued a desperate S.O.S. His city, one of America's most historic and gracious urban centers, had been devastated by Hurricane Katrina. Now eighty percent of it lay underwater, while some citizens huddled on rooftops waiting for rescue, and others turned the flooded streets into canals of anarchy. In the first decade of the 21st century, despair, disease and death had transformed a great American city into a scene of third-world privation. Heroic rescue workers battled to save lives, restore order and aid the suffering. Now Time chronicles the story of the greatest natural disaster in U.S. history in Hurricane Katrina, An American Tragedy. Here, in stunning pictures and gripping first-hand accounts, is the terrible tale of Katrina's deadly wrath and savage aftermath. Here is America's Gulf Coast--from New Orleans to Biloxi and Gulfport, Mississippi--in ruins. Here are the struggling survivors and their valiant rescuers, the looters and the police who fought to control them, the homeless refugees who poured across the southeast and the resourceful agencies that took them in. It is an epic tale, told as only Time can tell it. Award-winning pictures reveal the scope of the disaster. Oral histories offer unforgettable accounts of nature's power and man's resourcefulness. Illuminating graphics show how hurricanes form--and why New Orleans flooded. Powerful reporting puts readers on the scene, while insightful analysis explores the questions left in Katrina's wake: Could the tragedy have been prevented, and why was aid so late to arrive? Moving and informative, sweeping in scope and ringing with the voices of those who were there, Hurricane Katrina, An American Tragedy is the definitive account of a disaster that will haunt Americans for decades to come.